Hidrólise de atp e adp em líquor humano - Sperotto, Rita Leal (2008)
Adenine nucleotides hydrolysis is an important step of the neuromodulation of CNS and some of its breakdown products are able to protect the nervous tissue against brain injuries. The activity of NTPDase (EC 3.6.1.5, apyrase, CD39) was verified in cerebrospinal fluid (CSF) from patients without neural inflammatory process under different conditions and in the presence of several inhibitors. The samples were chose considering the low protein levels, normal glucose levels, low leukocyte count and CSF differential count. We chose use the supernatant 1 (S1) for enzyme assay due to the best enzymatic activities in this fraction. The best hydrolyze temperature was 37°C to ATP and ADP. This enzyme was cation-dependent, with a maximal rate for ATP and ADP hydrolysis in pH 8.0 in the presence of 5mM Ca+2. Sodum azide inhibited both nucleotide hydrolysis at concentrations higher than 10 mM. Sodium fluoride inhibited the ATP and ADP hydrolysis at concentrations of 15 mM and 20 mM. The Na+ K+ ATPase inhibitor ouabain, did not affect ATP or ADP hydrolysis. The inhibitor P-type ATPase lanthanum 5mM was ineffective on ATPDase hydrolysis. Suramin (30-300 μM) inhibited ATP and ADP hydrolysis and presented a maximal inhibitory effect of 50% at 300 μM. The results of the present study demonstrated that ATP and ADP hydrolysis from human CSF presented a similar response those obtained from rat synaptosomes.